The impact of macroeconomic variables on the Indonesian stock market volatility: conventional vis-a-vis Islamic stock market - Surur, Miftaskhus; Abdul Razak, Dzuljastri; Abduh, Muhamad (2012)
This study aims to explore the impact of macroeconomic variables towards the volatility of conventional and Islamic stock market in Indonesia by using Vector Autoregression and Vector Error Correction Model. The macroeconomic variables employed in the study are money supply, interest rate, exchange rate, income and inflation within the period of 2000:7 to 2011:12. The empirical findings indicate that the macroeconomic variables seem to be better explaining the Islamic stock price volatility than the conventional one. Moreover, the Islamic stock market indices need to shorter time to adjust the volatility when there is a shock in macroeconomic factors. However, from economic point of view, the volatility of Islamic stock markets indicates that the prices of Islamic stocks are reflecting the real economic activities. It is also revealed that the investing conducts of Muslim investors are really under ‘true investment behavior’ and more efficient market condition.